2000
DOI: 10.1016/s0893-133x(00)00085-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Estrogen-Receptor Directed Drugs of 5-Hydroxytryptamine-2A Receptors in Rat Brain

Abstract: Hormonal specificity of modulation of brain 5-HT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 29 publications
3
48
3
Order By: Relevance
“…Moreover, we reported that tamoxifen, in contrast to estradiol and raloxifene, has no significant modulatory effect on brain serotonin 5-hydroxytryptamine-2A receptors of ovariectomized rats , in most brain regions investigated (Cyr et al 2000b).…”
Section: Nmda Receptors Mrna Levelsmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, we reported that tamoxifen, in contrast to estradiol and raloxifene, has no significant modulatory effect on brain serotonin 5-hydroxytryptamine-2A receptors of ovariectomized rats , in most brain regions investigated (Cyr et al 2000b).…”
Section: Nmda Receptors Mrna Levelsmentioning
confidence: 87%
“…We have previously reported that estradiol increases 5-hydroxytryptamine-2A receptor density and expression in rat brain and that raloxifene mimics the effect of estradiol (Cyr et al 2000b). Moreover, we reported that tamoxifen, in contrast to estradiol and raloxifene, has no significant modulatory effect on brain serotonin 5-hydroxytryptamine-2A receptors of ovariectomized rats , in most brain regions investigated (Cyr et al 2000b).…”
Section: Nmda Receptors Mrna Levelsmentioning
confidence: 94%
See 1 more Smart Citation
“…Estradiol affects the availability and actions of serotonin by regulating the degradation of monoamine oxidase enzyme 16 and the expression of serotonin transporters, 5HT2A receptors and tryptophan hydroxylase enzyme 5,27 . Raloxifene and estradiol enhance the central serotonergic tone 5,27 , tamoxifen does not 28 and even may block some of the mechanisms involved in the regulation of serotonin uptake by estradiol 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol restores these levels to normal (Cyr et al, 2000b). Therefore, hormone-induced alterations in the serotonergic system cannot be excluded as contributors to the changes in parvalbumin expression seen in the current studies.…”
Section: Limitations and Future Directionsmentioning
confidence: 69%